Performance investigation on a novel spectral splitting concentrating photovoltaic/thermal system based on direct absorption collection. (15th March 2018) - Zhang, Gaoming; Wei, Jinjia; Xie, Huling; Wang, Zexin; Xi, Yonghao; Khalid, Muhammad
Highlights: A novel spectral splitting CPV/T prototype coupled a truncated CPC was set up. A radiation transfer model combined the concentrator and the filter was proposed. An electrical model was developed based on the discrete wavelengths method. The effect of concentration ratio was studied with and without spectral splitting. Abstract: The photovoltaic unit and the thermal unit are coupled in a concentrating photovoltaic/thermal (CPV/T) system and solar cells always operate at high temperature in order to obtain high quality thermal energy, which results in the overheating problem of solar cells. In the present study, a novel spectral splitting concentrating photovoltaic/thermal (SS-CPV/T) prototype based on direct absorption collection had been set up. The concentrator in the system is a truncated CPC by eliminating multiple reflections of solar radiation (called EMR), which was designed by our group. Water is used as both spectral splitting medium and heat transfer fluid in the spectral splitting subsystem. Distribution of the incidence angle of the irradiance illuminating on the filter at the outlet aperture of EMR was considered. The radiation transfer model was established to obtain the optical performance of the filter. And the electrical-thermal coupled model was proposed to predict the electrical and thermal performances of the SS-CPV/T system. When the total solar irradiance was about 1000 W/m 2 and the diffuse irradiance ratios were 15.0%, 17.8% and 24.0% respectively, the experimental electrical efficiencies of the SS-CPV/T system were 9.6%, 9.4% and 9.0% respectively and the thermal efficiencies were 52.0%, 50.7% and 48.5% respectively. The theoretical electrical efficiencies were 10.4%, 10.2% and 9.8% respectively and the theoretical thermal efficiencies were 52.8%, 51.5% and 49.4% respectively. Comparison experiments on the electrical and thermal performances of the CPV/T systems with and without spectral splitting were also conducted. Under the condition of the same outlet fluid temperature the maximum temperature of solar cells in the SS-CPV/T system was about 5.6 °C lower than the temperature of outlet fluid and about 12 °C lower than the maximum temperature of solar cells in the CPV/T system without spectral splitting. Finally, the theoretical model was expanded to higher concentration ratios to study the effects of the concentration ratio on the electrical and thermal performances of the CPV/T systems with and without spectral splitting. The results illustrate that compared to the CPV/T system without spectral splitting, the SS-CPV/T system has higher electrical efficiency when the concentration ratio is larger than 10 and higher exergy efficiency when the concentration ratio is larger than 14 for the outlet fluid temperature of 50 °C. And for 70 °C outlet fluid temperature, these two concentration ratios shift to 9 and 15 respectively. Thus, spectral splitting technology is more advantageous in the CPV/T systems with moderate and high outlet fluid temperature and concentration ratios.